Understanding the adoption of soil and water conservation practices: the role of social capital - Musoke, Elizabeth (Kansas State University, 2017)
Kenya has been adversely affected by soil erosion due to population growth, changes in land use and land cover, and unsustainable agricultural practices. Issues related to land degradation cost the Kenyan government approximately $390 million or 3 percent of the country’s GDP yearly (Government of Kenya, 2013). Despite extensive land degradation, many attempts to encourage the use of soil and water conservation (SWC) practices have been unsuccessful. The study focuses on Merigi Ward, Kenya. Merigi Ward lies within the Mara River Basin (MRB), an ecologically and economically important river basin that has experienced extensive erosion problems. Increased agricultural activities driven by population growth in the area and changes in land use and land cover have degraded the landscape. SWC practices are greatly needed to mitigate the effects of erosion and conserve the natural resources within the MRB. Past studies suggest that social capital may increase the adoption of SWC practices (Knowler & Bradshaw, 2007; Nyangena, 2008). This study defines social capital as the groups and networks, trust and reciprocity, formal and informal rules, and information that informs the interactions among persons that lead to collective action. Twenty-five smallholder farmers within Merigi Ward were interviewed and the relationship between the adoption of SWC practices and social capital was explored through a qualitative analysis. Additionally, the MRB is home to the Mau Mara Serengeti Sustainable Water Initiative (MaMaSe). The MaMaSe initiative is a public private partnership (P3) with the goal to promote sustainable water use, economic growth, and environmental conservation within the basin. The effect the MaMaSe initiative had on the level of social capital amongst the study participants was also investigated. Findings suggest that social capital is an important aspect of SWC adoption in Merigi Ward. Groups and networks provide farmers with implementation support and information. Particularly, the local farmers’ cooperative provides farmers with implementation assistance and links (bridging capital) to experts at the MaMaSe initiative and the Ministry of Agriculture. Strong bonding capital works in the favor of this community allowing for high levels of trust. Thus, farmers collaborate to help one another implement practices and exchange information, materials, and experiences. In general, social capital has helped facilitate better environmental conservation awareness and the use of SWC practices. The largest impact the MaMaSe initiative had on the community’s social capital was expanding networks (particularly bridging and linking capital) and providing in depth information and guidelines for SWC practice use. The P3 has also helped the farmers integrate environmental conservation into their daily lives and has helped promote a shared understanding of the importance of conservation. The findings of this study will help environmental conservation professionals understand how to use social capital to strengthen natural resource management.
Keywords: Soil and water conservation; Social capital; Mara River Basin